Evaluasi Multidimensi Keberlanjutan Usahatani Padi Sawah Serta Karakteristik Petani di Kecamatan Bangkinang Kabupaten Kampar - Nurhidayati Nurhidayati; Evy Maharani; Sispa Pebrian (Universitas Galuh, 2026)
Lowland rice farming plays an important role in supporting food security; however, its sustainability faces various ecological, economic, and social challenges. This study aimed to analyze the characteristics of lowland rice farmers and evaluate the multidimensional sustainability status of lowland rice farming in Bangkinang District, Kampar Regency. The research was conducted in Bangkinang District Villages using a survey method involving 50 rice farmers selected through simple random sampling. Descriptive analysis was used to describe farmer characteristics, while sustainability analysis was carried out using the Multidimensional Scaling (MDS) method with the Rap-Paddy software. The results showed that rice farmers were predominantly 40-55 years old, had junior to senior high school education, possessed 10-20 years of farming experience, and managed land areas ranging from 0.26 to 0.50 ha. The multidimensional sustainability index of lowland rice farming was 54.18, indicating a moderately sustainable status. Partially, the ecological dimension scored 47.85 (less sustainable), the economic dimension scored 52.37 (moderately sustainable), and the social dimension scored 62.31 (moderately sustainable). Sensitive attributes affecting sustainability included pest and disease control, marketing structure, farm productivity, farmer regeneration, family participation, and the intensity of extension activities. Improvements in these attributes are necessary to enhance the sustainability of lowland rice farming in Bangkinang District.